Analysis of the Theory of Learning Tawhid from the Perspective of Islamic Religious Education Psychology - Andika Kayadi; Muhammad Aufakumara Sucipt; Firman Facatle (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the theory of monotheistic learning from the perspective of Islamic religious education psychology. The research method used is qualitative with a literature review study approach. Furthermore, the moral crisis that is precipitated according to the researcher. Therefore, the researcher analyzes the theory of learning from the perspective of Islamic religious education psychology as a solution. Related to the phenomenon of moral crisis that leads to character education, there are several solutions that can be applied, including the theory of monotheistic learning which invites individuals to know and understand the importance of knowledge about the Oneness of God, that there is no God other than Allah. This theory will encourage the improvement of morality by emphasizing the importance of family and parents. There are several methods in this theory, including the cognitive approach, where people focus their attention on information, understanding, application, analysis, evaluation, and creation. Individuals will then take an affective-approach, focusing on receiving, responding, enjoying, and practicing. Finally, in the psychomotor method, individuals will focus on paying attention, asking questions, reasoning and communicating.